Electronic, charge and magnetic interactions in three-centre systems1. Issue 18 (14th May 2015) - Paretzki, Alexa; Hübner, Ralph; Ye, Shengfa; Bubrin, Martina; Kämper, Sara; Kaim, Wolfgang
<x xml:space="preserve">Abstract</x> Variable kinds of coupling have been observed for copper–bis(radical) complexes.